Tantangan demokrasi di era media sosial - Arga Prakarsa, Alfan Rizqana (Maliki Interdisciplinary Journal, 2026)
The rapid growth of social media has fundamentally transformed the democratic landscape in many countries, including Indonesia. While digital platforms provide new spaces for citizens to participate in political discourse, monitor governance, and express their aspirations more broadly and rapidly, their viral nature also creates opportunities for misinformation, disinformation, opinion polarization, and political manipulation. This article critically examines the challenges facing democratic systems due to the massive use of social media, focusing on the mechanisms of public opinion formation, the phenomena of filter bubbles and echo chambers, and the erosion of public trust in democratic institutions. Using a descriptive-analytical literature review method, the study finds that social media is a double-edged sword: it strengthens participation while also becoming fertile ground for threats to democratic integrity. Strengthening digital literacy, balanced platform regulation, and multi-stakeholder collaboration are essential to safeguard democracy in the digital age.